THE POTENTIAL OF FALOAK BARK (STERCULIA QUADRIFIDA R.BR.) as an ACTIVATED CARBON PRODUCT THROUGH PHYSICAL-CHEMICAL ACTIVATION METHOD - Bobu, Fetronela Rambu; Tea , Marselina Theresia Djue; Donuata, Pujianti Bejahida; Batu, Matius Stefanus (Universitas Mataram, 2025)
Faloak is a plant species native to the East Nusa Tenggara region and Australia, widely used by the local community in NTT as an herbal medicine, particularly in treating liver disease, digestive disorders, and fatigue. However, this study presents a new application by analyzing its physical-chemical properties and evaluating its effectiveness in the synthesis of activated carbon. This study aims to explore and analyze the potential of Faloak bark as a source of activated carbon, which has not been examined in previous research. This research uses a quantitative approach by conducting controlled laboratory experiments to measure and analyze the variation in activator concentration on the water and ash content of activated carbon. The research applied the physical-chemical activation method. The physical activation process involved heating at temperatures ranging from 250°C to 450°C, while chemical activation was conducted using ZnCl₂ and NaOH at concentrations of 1 N, 2 N, and 3 N. This method was selected to determine the optimal conditions for converting Faloak bark into activated carbon, focusing on temperature and chemical activators. The findings indicate that the optimum temperature for activated carbon formation is 300°C. Additionally, tests using chemical activators showed that Faloak bark performs best with a 2 N NaOH solution, as evidenced by ash and water contents of 0.03% and 0.65%, respectively. Functional group analysis through FTIR testing identified the presence of (hydroxyl), aromatic C=C, and carbonyl C=O groups, further supporting the potential of Faloak bark as a viable material for activated carbon production. The findings suggest that Faloak bark has significant potential to be developed into an activated carbon product.